Corporate Social Responsibility and Organization Performance - Nansubuga Suubi Anne (UCU, 2024)
This study explores the relationship between Corporate Social Responsibility (CSR) and organizational performance, with a specific focus on Stanbic Bank Uganda. The research investigates how CSR initiatives impact various performance measures within the bank, including financial literacy campaigns, community and sustainability programs, and educational support. Utilizing a qualitative research design, the study utilizes questionnaires as a data collection tool. Findings indicate that CSR activities, such as community development projects and environmental sustainability efforts, financial literacy campaigns and educational support have positively influenced organizational performance and are essential for strategic decision making. The results highlight that CSR initiatives contribute to enhanced brand reputation, increased customer trust, and improved employee morale, which in turn drive better financial performance. The findings reveal that financial literacy programs help customers make informed decisions therefore increasing customer satisfaction and retention and ensuring long term viability. It was also discovered community and environmental sustainability programs serve as a crucial component of CSR, influencing both corporate reputation and operational efficiency. The study further reveals that educational support programs are useful in addressing the skills gaps. The combination of these variables demonstrates that a well-structured CSR strategy can lead to better organizational performance by improving financial outcomes, promoting sustainability and fostering educational development. This dissertation highlights the need for organizations to strategically integrate CSR into their businesses to fully realize its advantages and contribute positively to society and the study concludes with recommendations for developing a CSR policy that is comprehensive in nature to maximize both social impact and organizational success.